2018
DOI: 10.12659/msmbr.909200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mental Well-Being and Reduced State Anxiety in Teachers After Participation in a Residential Yoga Program

Abstract: BackgroundReducing stress in the workplace improves mental health. Teaching is of social importance, but it may receive inadequate recognition and rewards. The present study compared mental well-being and state anxiety in primary school teachers who practiced 15 days of yoga in a residential setting with those who continued their usual routine.Material/MethodsWe enrolled 236 primary school teachers to participate in the study. We assigned 118 primary school teachers (group mean ±S.D., age 41.5±6.0 years, 74 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 39 publications
2
48
0
1
Order By: Relevance
“…While China and Pakistan are culturally different from India, there are many sociocultural aspects that influence mental wellbeing that are similar. The WEMWBS has been previously used in Indian populations [15,23]. The WEMWBS is a fourteen-item scale that asks people to describe their experience of feelings and thoughts over the last two weeks with five possible options as their response: 1, never; 2, rarely; 3, sometimes; 4, often; and 5, very often.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While China and Pakistan are culturally different from India, there are many sociocultural aspects that influence mental wellbeing that are similar. The WEMWBS has been previously used in Indian populations [15,23]. The WEMWBS is a fourteen-item scale that asks people to describe their experience of feelings and thoughts over the last two weeks with five possible options as their response: 1, never; 2, rarely; 3, sometimes; 4, often; and 5, very often.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with conventional care, yoga significantly improved health-related quality of life and exercise capacity [14]. Apart from the studies of quality of life in patients, mental wellbeing was found to improve wellbeing in 118 healthy primary school teachers after fifteen days of an intensive residential yoga [15].…”
Section: Introductionmentioning
confidence: 99%
“…Other research established a cutoff of 8, (sensitivity 77%, speci city 82%) as a screener for panic disorder, social anxiety phobia and PTSD [25]. GAD-7 scores were totaled and classi ed as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14) and severe (15)(16)(17)(18)(19)(20)(21) [24], and strati ed into two groups (< 8 or > 8) as a cut-off for panic disorder and social anxiety phobia [25].…”
Section: Anxietymentioning
confidence: 99%
“…Parent and teacher observations are important in screening children for emotional disorders [15,16]. As observers, parents and teachers can positively in uence children's well-being [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is known to positively influence physical and mental well-being [8]. Previously, the same authors assessed primary school teachers in India (n = 118, both sexes) who, after 15 days of yoga in a residential setting had an increase in mental well-being (small Cohen’s d effect size = 0.36) and a decrease in state anxiety (small Cohen’s d effect size = 0.25), compared to an equal number of their colleagues who carried on with their routine [9].…”
Section: Introductionmentioning
confidence: 99%